E-book-based Teaching Materials for Novel Texts Oriented to Local Culture for High Schools - Ririn Wulandari; Sobihah Rasyad; Juwanda (Widyantara, 2023)
This study was motivated by the limited teaching materials used by students and teachers. Teachers only use teaching materials published by the government. In addition, the learning of novel texts that raise the value of Cirebon culture is not illustrated in printed books. This is evidenced by the results of the analysis of printed books that have been carried out by the author. To overcome this, it is necessary to have alternative teaching materials for the teaching and learning process in the classroom. In the process of preparing teaching materials, there are 3 stages, namely pre-writing, writing, and post-writing. The research method used is research and development with data collection techniques in the form of questionnaires, interviews, and observations. The results of this study show that the learning design in teaching materials consists of introduction, content, and closing. In addition, the results of the validation questionnaire showed a percentage of 92.85% in terms of material, and 92.5% in terms of media. The percentage shows that the teaching materials for novel texts are very valid. In the implementation process, this research has 3 stages, namely, student responses, formative test results, and the results of interviews with teachers.